Igbin musical tradition in Yoruba culture (2013)
The Yoruba of South-western Nigeria like many African societies since the pre-colonial era have paid great attention to their cultural practices including traditional worship of deities such as sango, osun, esu, ogun, obatala and so forth. In the Yoruba worldview, religious worship remains a major avenue of communing and renewing relationship with the spirit world in order to maintain cosmological equilibrium. Activities connected with act of worship often involve the use of music and musical instruments. While much is known about numerous Yoruba traditional drums such as the dundun, bata, bembe, gbedu and so forth, little is known about igbin musical performances in the society. This paper, therefore, examines igbin orisa musical tradition and its place in Yoruba society. The igbin ensemble consists of three drums namely iyaalu, omele-ako and omele-abo. Besides the usual musical function, the ensemble typifies the family as the central unit upon which the Yoruba society is anchored. Effects of acculturation resulting in a shift from traditional worship to other religions especially Christianity and Islam as well as erosion of societal values were also identified. Drawing examples from the organisation and performance practices of Igbin music in Yoruba culture, the paper argues that African musicology could make more meaningful contributions including knowledge preservation and promotion of African cultural heritage beyond mere documentation which had hitherto characterised the discipline.